Neoadjuvant Radiotherapy Dose Escalation in Locally Advanced Rectal Cancer: a Systematic Review and Meta-analysis of Modern Treatment Approaches and Outcomes. Issue 1 (January 2021) - Hearn, N.; Atwell, D.; Cahill, K.; Elks, J.; Vignarajah, D.; Lagopoulos, J.; Min, M.
Abstract: Aims: Improving pathological complete response (pCR) rates after neoadjuvant chemoradiotherapy for locally advanced rectal cancer may facilitate surgery-sparing treatment paradigms. Radiotherapy boost has been linked to higher rates of pCR; however, outcomes in moderately escalated inverse-planning studies have not been systematically evaluated. We therefore carried out a systematic review and meta-analysis of radiation dose-escalation studies in the context of neoadjuvant therapy for locally advanced rectal cancer. Materials and methods: A systematic search of Pubmed, EMBASE and Cochrane databases for synonyms of 'rectal cancer', 'radiotherapy' and 'boost' was carried out. Studies were screened for radiotherapy prescription >54 Gy. Prespecified quality assessment was carried out for meta-analysis inclusion suitability. Pooled estimates of pCR, acute toxicity (grade ≥3) and R0 resection rates were determined with random-effects restricted maximum-likelihood estimation. Heterogeneity was assessed with Higgins I 2 and Cochran Q statistic. Subset analysis examined outcomes in modern inverse-planning studies. Meta-regression with permutation correction was carried out for each outcome against radiation dose, radiotherapy technique, boost technique, chemotherapy intensification and other patient- and treatment-related cofactors. Results: Forty-nine primary and three follow-up publications were included in the systematic review. Pooled estimates of pCR, toxicity and R0 resection across 37 eligible publications ( n = 1817 patients) were 24.1% (95% confidence interval 21.2–27.4%), 11.2% (95% confidence interval 7.2–17.0%) and 90.7% (95% confidence interval 87.9–93.8%). Within inverse-planning studies (17 publications, n = 959 patients), these rates were 25.7% (95% confidence interval 21.0–31.1%), 9.8% (95% confidence interval 4.6–19.7%) and 95.3% (95% confidence interval 91.6–97.4%). Regression analysis did not identify any significant predictor of pCR ( P > 0.05). Conclusions: Radiotherapy dose escalation above 54 Gy is associated with high rates of pCR and does not seem to increase the risk of acute grade ≥3 toxicity events. pCR rates approaching 25% may be achievable utilising moderate escalation (54–60 Gy) with modern inverse-planning techniques; however, a clear dose–response relationship was not identified in regression analysis and additional evidence is awaited given the prevalence of heterogenous single-arm studies to date.